Transient Assay for Promoter Activity of Metallothionein-Like Gene from Oil Palm in Driving Tissue-Specific Expression of Polyhydroxybutyrate and Reporter Genes - Omidvar, Vahid (2006)
Polyhydroxybutyrate is the most important type of polyhydroxyalkanoates (PHA), which is naturally synthesized by several microorganisms. Production of PHB in plants is based on the consumption of acetyl-CoA as an initial substrate, therefore oil palm being an oil crop serve as potential target due to its high flux of acetyl-CoA during the oil synthesis stage. In oil palm, mesocarp is the specialized tissue for oil synthesis. Targeting the expression of PHB genes in mesocarp tissue requires the mesocarp-specific regulation of these genes by a mesocarp-specific promoter, since accumulation of PHB in other tissues may have deleterious effects on the plant. Pervious efforts have resulted in isolation of promoter sequence of the oil palm mesocarp-specific metallothionein-like gene (designated MSP1) and preparation of the gene construct carrying PHB genes (pMS29 vector) to drive the specific expression of PHB genes (phbA, phbB, and phbC) in mesocarp tissue.